Influence of Platelets and Platelet Microbicidal Protein Susceptibility on the Fate of Staphylococcus aureus in an In Vitro Model of Infective Endocarditis - Mercier, Renee-Claude (American Society for Microbiology, 2000)
Several lines of evidence indicate that platelets protect against endovascular infections such as infective endocarditis (IE). It is highly likely that a principal mechanism of this platelet host defense role is the release of platelet microbicidal proteins (PMPs) in response to agonists generated at sites of endovascular infection. We studied the ability of platelets to limit the colonization and proliferation of Staphylococcus aureus in an in vitro model of IE. Three isogenic S. aureus strains, differing in their in vitro susceptibility to thrombin-induced platelet microbicidal protein-1 (tPMP), were used: ISP479C (parental strain; highly susceptible to tPMP [tPMP(s)]); ISP479R (transposon mutant derived from ISP479; tPMP resistant [tPMP(r)]); or 757-5 (tPMP(r) transductant of the ISP479R genotype in the ISP479 parental background). Time-kill assays and in vitro IE models were used to examine the temporal relationship between thrombin-induced platelet activation and S. aureus killing. In time-kill studies, early platelet activation (30 min prior to bacterial exposure) correlated with a significant bactericidal effect against tPMP(s) ISP479C (r(2) > 0.90, P < 0.02) but not against tPMP(r) strains, ISP479R or 757-5. In the IE model, thrombin activation significantly inhibited proliferation of ISP479C within simulated vegetations compared to strains ISP479R or 757-5 (P < 0.05). The latter differences were observed despite there being no detectable differences among the three S. aureus strains in initial colonization of simulated vegetations. Collectively, these data indicate that platelets limit intravegetation proliferation of tPMP(s) but not tPMP(r) S. aureus. These findings underscore the likelihood that platelets play an important antimicrobial host defense role in preventing and/or limiting endovascular infections due to tPMP(s) pathogens.